Peningkatan Aktivitas Belajar Mahasiswa Pada Mata Kuliah Kimia Instrumentasi Menggunakan Pembelajaran Berbasis Proyek Secara Online - Susanto, Nindita Clourisa A; Rahmi, Rahmi; Lestari, Intan; Sutrisno, Sutrisno (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Learning in the 4.0 revolution era requires teaching staff to prepare innovative and creative learning models and methods according to students' needs. To meet these needs, the role of technology is needed in its implementation. An online learning system via LMS is the right solution for today's students. To foster collaboration between students and increase learning activities, a project-based learning model was chosen. Teaching materials were developed using Dick and Carey's development design through several stages leading to formative evaluation. The resulting product is then implemented in large lecture classes. The results of the implementation show that there has been an increase in student learning activities when implementing this learning. The percentages of each activity in sequence are giving consideration activities reaching 95.15%, training activities reaching 91.21%, interpreting activities reaching 71.96%, applying activities reaching 68.30%, evaluating activities reaching 66.18%, and creative activity reached 51.24%. The results of student learning activities show a tendency for students' thinking structures from easy things to difficult things.